Nuclear physics - Ghoshal, S. N. (New Delhi: S Chand, 1994)
This well-written text discusses the principles and concepts of Nuclear Physics in a simple and easy-to-understand language. It discusses the structure and properties of atomic nucleus, radioactivity, nuclear radiations, nuclear models, nuclear reactions and accelerators of charged particles. The book also discusses nuclear forces & two-body problem, elementary particles and cosmic rays. It would be extremely useful for undergraduate and postgraduate students of Physics.
Index 1048-1055p.
Keywords: Nuclear physics; Physics; General Science